Uncovering the binding of the anticancer small molecule SLMP53-1 to mutant p53R280K - Gomes, A. S. (2017)
Introduction: The tumor suppressor protein p53 is frequently mutated in human cancer, which is commonly related to poor prognosis. Thus, reactivation of wild-type functions to mutant p53 is an attractive anticancer therapeutic strategy (1). Indeed, many efforts have been developed to target mutant p53. In a recent work, our group discovered the small molecule SLMP53-1, which restores the wild-type activity to mutant p53R280K with promising in vitro and in vivo antitumor activity results (2; 3). Aims: The present work aims to unravel the binding of SLMP53-1 to mutant p53R280K. Materials and methods: With that purpose, two strategies were defined: i) to assess the thermal stabilization of mutant p53R280K, induced by the binding of SLMP53-1 to mutant p53, in a cellular context by Cellular Thermal Shift Assay (CETSA); and ii) to produce p53R280K for biophysical binding assays, including MicroScale Thermophoresis (MST), Saturation-Transfer Difference NMR (STD-NMR) and X-ray crystallography. Results: By CETSA, we showed that SLMP53-1 induces p53R280K thermal stabilization, confirming the binding of SLMP53-1 to p53R280K. Recombinant p53R280K protein (core domain) was successfully produced and purified from E. coli BL21(DE3). So far, crystals of apo p53R280K and with SLMP53-1 were obtained. Co-crystallization optimization, MST and STD-NMR experiments are underway. Conclusions: With this work, the SLMP53-1 binding to p53R280K was confirmed and its characterization is in progress. This integrated study will contribute to understand the biology and pharmacology of p53 mutant forms and to the rational design of improved reactivators of mutant p53.